The Effectiveness of Cross-Age Blogging - Beth Walizer (The Advocate, 2014)
Introduction:“We didn’t have to do any work!” was the greatest response to the question asked of fourth and fifth-grade students on what they liked best about the month long cross-age buddy reading and blogging project. A major challenge of candidates and university faculty in teacher education is how to effectively develop children’s digital literacy skills.